2022
DOI: 10.1017/s0014479721000302
|View full text |Cite|
|
Sign up to set email alerts
|

Yield-limiting plant nutrients for maize production in northwest Ethiopia

Abstract: Summary The potential yield of improved maize varieties usually cannot be fully realised mainly due to inappropriate soil nutrient management practices in most parts of Ethiopia. Site-specific fertiliser recommendations are rarely used in the farming systems of Ethiopia. There is also a lack of data to develop or validate decision support tools for targeting specific crop production. A study was conducted for three consecutive rainy seasons (2016–2018) in the maize belt of the north-western parts of the Amh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
4
6
0
Order By: Relevance
“…Accordingly, the soils of Yilmana Densa were below the critical levels of SOC, whereas those of south Gondar ranged from below to critical levels ( Loveland and Webb, 2003 ; Murphy, 2014 ). It was similar with other findings for the cultivated lands of Ethiopia ( Amare et al., 2022a , 2022b ; Amare, 2018 ; Amare et al., 2013a , b ). Generally, soils of the study areas were low in SOC that limits the supply of nutrients including N and P ( Murphy, 2014 ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Accordingly, the soils of Yilmana Densa were below the critical levels of SOC, whereas those of south Gondar ranged from below to critical levels ( Loveland and Webb, 2003 ; Murphy, 2014 ). It was similar with other findings for the cultivated lands of Ethiopia ( Amare et al., 2022a , 2022b ; Amare, 2018 ; Amare et al., 2013a , b ). Generally, soils of the study areas were low in SOC that limits the supply of nutrients including N and P ( Murphy, 2014 ).…”
Section: Resultssupporting
confidence: 92%
“…(2019) also used the rates of N and P (138–151 N and 69–75 kg P 2 O 5 ha −1 ), which are similar to our findings and recommendations. In general, the yield of potato at Yilmana Densa could be improved by more than threefold (greater than 300%) and at South Gondar by more than two and a half-fold (greater than 250%) through nutrient applications (N) that is in line with the findings of Amare et al (2022a , b ), they reported that omitting nitrogen resulted in a non-significant yield of maize with no nutrient applications, regardless the high rates of phosphorus and potassium.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…This suggests that nitrogen is the primary limiting nutrient in the study sites, as nitrogen application had a more significant impact on yield compared to phosphorus. Amare et al [ 35 ] provided supporting evidence that nitrogen fertilizer is the primary and most significant yield-limiting nutrient, followed by phosphorus, confirming the idea that the decline in soil fertility affects crop production. Likewise, Alemayehu et al [ 36 ] and Chala et al [ 7 ] reported similar findings in their studies.…”
Section: Resultsmentioning
confidence: 91%
“…The responses to fertilizer application varied across geographical locations (Amare et al., 2018; Tamene et al., 2017) and environments. Fertilizer applications should consider landscape positions on soils with undulating topographic features (Amede et al., 2020).…”
Section: Introductionmentioning
confidence: 99%